The rationality of suicide - Chandrasekaran, Vaishgnavi (2018)
This paper discusses the rationality of suicide. Specifically, it will be argued that there are certain circumstances in which suicide can be rational. I will argue that Physician-Assisted Suicide, Voluntary Euthanasia, and Self-Accomplished Deaths are all forms of suicide. Throughout the paper, I will respond to some objections to the rationality of these forms of suicide. These objections will include ‘Respecting Dignity and Humanity’, ‘Slippery Slope’, the presence of mental illness, inability to think clearly, ‘Two-State Requirement’ and the ‘Crystal Ball’ account. I will argue that none of them succeed as a justificatory reason in classifying suicide as an irrational act. This will therefore allow for the conclusion that suicide is indeed rational in certain circumstances.